MOTIVASI PELAKSANA TUGAS KEPALA SEKOLAH DALAM MELAKSANAKAN FUNGSI MANAJEMEN KEPEMIMPINAN DI SMA NEGERI 2 TENGGARONG - beauty kusnukiandany, intan; umi puspita sari, friska; Faradila Nur, Syalma; Aulia Mahmud, Dini; Hanggara, Anggy; Romaida Efrianti Br Situmorang, Yustina; Herwin; Komariyah, Laili; Dwiyono, Yudo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Acting School Principal faces the challenge of increased responsibilities. This is especially true for teachers who are given the additional task of serving as acting school principal. This challenge can affect their work motivation because their workload increases, which also means their responsibilities grow. Such conditions can impact the effectiveness of the leadership management function due to the work motivation of an acting school principal who is temporarily filling the position. This study uses a qualitative method with a case study design aimed at understanding how acting school principals interpret their roles, the strategies they use to manage the school organization, how management functions are applied, and how motivation influences daily leadership actions. The results show that the Acting Principal of SMA Negeri 02 Tenggarong has high motivation in carrying out leadership functions, performs responsibilities by implementing management functions (planning, organizing, actuating, controlling), and there are supporting and inhibiting factors in carrying out their duties.